PENGARUH UKURAN DEWAN PENGAWAS SYARIAH DAN ISLAMIC CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (Studi Pada Bank Umum Syariah Periode 2015-2019) - Khasanatul Lailiyah; Maslichah Maslichah; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This research is used to analyze the influence of the size of the supervisory board of sharia and Islamic Corporate Governance, which is proxied by Investment Account Holders, the duties and responsibilities of DPS and sharia compliance on the for 2015-2019. Sample in this study consisted of 10 companies with 50 total data. The method of analysis in this study uses multiple regression analysis. Based on the results of the simultaneous testing, it is known that and Islamic corporate governance has an effect on ISR disclosure and partially the size of the sharia supervisory board has a negative effect and IAH has a positive effect on ISR disclosure, while SSB's duties and responsibilities and Sharia compliance do not affect ISR disclosure in commercial banks. Sharia is registered by the Financial Services Authority for the period 2015-2019.Keywords : Sharia supervisory board size, Islamic corporate governance, Islamic social reporting disclosures